Beef cattle commercial feedlot studies Trial 1—Effects on steer performance of variable protein levels, implanting, and worming - Jack G. Riley; K.F. Harrison; D.L. Good (Kansas Agricultural Experiment Station Research Reports, 1973)
A 112-day trial used 280 mixed-breed yearling steers to study effects of varying protein levels in finishing steers rations. Crude protein content ranged from 15.1 percent for the first 28 days to 8.9 percent crude protein the final 28 days. Feeding a 15.1% crude protein ration for 28 days and a 13.2% crude protein ration the second 28 days or feeding a 13.2% crude protein ration for the first 56 days did not significantly improve total gain compared with feeding an 11.2% crude protein (control) ration.
Keywords: Cattlemen' s Day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station); 568; Beef; Commerical feedlots; Steer performance; Protein; Implants; Worming